2019
DOI: 10.1111/jora.12540
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Development in Adolescence: An Examination of Genetic and Environmental Influences

Abstract: Sexual development entails many experiences and is a major feature of adolescence. Most relevant behavioral genetic studies, however, focus primarily on sexual behaviors associated with health risks. We took a more normative, developmental perspective by examining genetic and environmental influences on five sexual behaviors ranging from dating to pregnancy in middle (M age = 14.90 years) and late adolescence (M age = 17.85 years) in a sample of twins (N = 3,762). Overall, behaviors that are more common and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Importantly, the results here are consistent with related studies about peer affiliations, personality and sexual behaviors in adolescence, which have shown that shared environmental influences largely accounted for the association between friend behaviors and less normative sexual behaviors (e.g., early sexual debut; Clark et al, 2020), and between behavioral undercontrol and less normative sexual behaviors (Clark et al, 2021). Taken together, this implies a set of environmental presses that push youth towards behavioral undercontrol, antisocial peer affiliations, and risky sex behaviors.…”
Section: Genetic and Environmental Influences On Personality And Peersupporting
confidence: 91%
“…Importantly, the results here are consistent with related studies about peer affiliations, personality and sexual behaviors in adolescence, which have shown that shared environmental influences largely accounted for the association between friend behaviors and less normative sexual behaviors (e.g., early sexual debut; Clark et al, 2020), and between behavioral undercontrol and less normative sexual behaviors (Clark et al, 2021). Taken together, this implies a set of environmental presses that push youth towards behavioral undercontrol, antisocial peer affiliations, and risky sex behaviors.…”
Section: Genetic and Environmental Influences On Personality And Peersupporting
confidence: 91%
“…Recently, we showed that item response theory (IRT) models can be used to operationalize a conceptualization of adolescent sexual behaviors as existing along a continuum of "difficulty" defined by their prevalence, providing a quantitative measure of an individual's level of sexual development (Clark et al, 2020). That is, less mature sexual behaviors such as kissing, petting, and dry sex will have lower difficulty values relative to more mature sexual behaviors that tend to occur at later ages such as oral, vaginal, and anal sex (Carver et al, 2003;Clark et al, 2020). For example, dating and kissing are relatively frequent romantic behaviors by middle adolescence and have been associated with positive behavioral correlates (Carver et al, 2003).…”
Section: Adolescent Sexual Developmentmentioning
confidence: 99%
“…This is consistent with the lower prevalence rate of anal sex relative vaginal and oral sex. That is, anal sex is a less common and more sexually advanced behavior and may require greater preparation compared to oral and vaginal sex [35]. This may pose a barrier to populations with limited access to certain sexual wellness resources (i.e., lubrication).…”
Section: Plos Onementioning
confidence: 99%